Cost-Effective Method for Dissolved Oxygen Sensing with Electrodeposited n-Cu2O Thin-Film Semiconductors - H. E. Wijesooriya; J. A. Seneviratne; K. M. D. C. Jayathilaka; W. T. R. S. Fernando; P. L. A. K. Piyumal; A. L. A. K. Ranaweera; S. R. D. Kalingamudali; L. S. R. Kumara; O. Seo; O. Sakata; R. P. Wijesundera (Physchem)
Dissolved oxygen (DO) is a crucial parameter in water quality monitoring because it directly affects the health of aquatic ecosystems. This study explored electrodeposited Cu2O thin-film semiconductors for DO sensing. Cu2O was chosen for its low cost, eco-friendliness, and non-toxic nature. Cu2O films were electrodeposited on titanium (Ti) substrates using an acetate bath (0.1 M sodium acetate and 0.01 M cupric acetate) at −200 mV versus Ag/AgCl for 30 min, with a bath temperature of 55 °C, stirred at 50 rpm. The bath pH was systematically adjusted from 5.8 to 6.8 in 0.2 steps using NaOH and Acetic acid. A range of analyses including synchrotron X-ray diffraction (SXRD), scanning electron microscopy (SEM), surface wettability, capacitance–voltage (C-V), Raman spectroscopy, Fourier-transform infrared (FTIR) spectrum, and Electrochemical Impedance Spectroscopy (EIS) was performed to assess their properties and sensing performance. The results showed that Cu2O films deposited at pH 6.4 exhibited optimal performance for DO sensing, with a strong linear response, marking this pH, deposition time, and temperature as ideal for creating effective DO sensors. This study introduces a novel, cost-effective approach to dissolved oxygen sensing using electrodeposited n-Cu2O thin-film semiconductors, marking the first application of this material in such sensors and showcasing its potential for scalable and environmentally sustainable sensing technologies.